2020
DOI: 10.15403/jgld-2765
|View full text |Cite
|
Sign up to set email alerts
|

Thioguanine Therapy in Inflammatory Bowel Diseases. A Practical Guide

Abstract: Thiopurine-derivates azathioprine and mercaptopurine are frequently used to maintain remission in inflammatory bowel diseases (IBD). Despite their efficacy, more than 50% of patients discontinue therapy, mainly due to the development of adverse events. Thioguanine is an alternative thiopurine and has been conditionally licensed in The Netherlands as IBD treatment for patients after conventional thiopurine therapy failure. In this review we will provide practical information on initiating and maintaining thiogu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 76 publications
(113 reference statements)
0
16
0
Order By: Relevance
“…6‐thioguanine, the third therapeutic formulation, bypasses the pathways mentioned above and can restore therapeutic efficacy in patients with ineffective metabolism. 5 …”
Section: Thiopurine Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…6‐thioguanine, the third therapeutic formulation, bypasses the pathways mentioned above and can restore therapeutic efficacy in patients with ineffective metabolism. 5 …”
Section: Thiopurine Metabolismmentioning
confidence: 99%
“…Thioguanine is used in a dose of 20 mg/day (0.2–0.3 mg/kg/day). 5 Once a feared complication of 6‐TG use, nodular regenerative hyperplasia is not associated with the lower dose used for IBD. Regarding efficacy, in a systematic review, TG treatment after AZA/6‐MP failure showed clinical improvement in 65% of patients.…”
Section: Genetic Polymorphisms Impacting Thiopurine Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, two nucleoside analogs, namely gemcitabine and 6-thioguanine, have a weak HDP-inducing activity as well. Both compounds work mainly by incorporating into DNA and RNA as fraudulent bases to cause termination of cellular synthesis of DNA/RNA and have been approved for treatment of cancers and inflammatory bowel diseases [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other out of fashion drugs such as purine can still be used. 45 Psychological alterations are managed by neuromodulators. Beside these drugs, surgical therapy can be considered in special cases.…”
Section: Discussionmentioning
confidence: 99%